2003
DOI: 10.1097/01.asn.0000098700.70804.d3
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Regulates the Na+/H+ Exchanger 3 in OKP Cells

Abstract: Abstract. Albumin filtered by the glomerulus is reabsorbed in the proximal tubule. We have shown previously that proteinuria stimulates the proximal tubular Na ϩ /H ϩ exchanger 3 (NHE3) in rats. Activation of NHE3 may be a pathophysiologically important factor in the development of renal salt and water retention observed in the nephrotic syndrome. For examining whether albumin is a specific inducer of proximal tubular Na ϩ /H ϩ exchange and to determine the molecular mechanisms by which it regulates Na ϩ /H ϩ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…However the present in vitro studies on NHE3 was preceded by a recent study from the same group that demonstrated that the PAN model of nephrosis increases NHE3 in vivo (12). The current studies by Klisic et al (1) show that NHE3 is activated in vitro at several levels (functional activity, mRNA, trafficking) by albumin. There is a complicated interaction with hydrocortisone, which itself activates NHE3 at multiple levels.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…However the present in vitro studies on NHE3 was preceded by a recent study from the same group that demonstrated that the PAN model of nephrosis increases NHE3 in vivo (12). The current studies by Klisic et al (1) show that NHE3 is activated in vitro at several levels (functional activity, mRNA, trafficking) by albumin. There is a complicated interaction with hydrocortisone, which itself activates NHE3 at multiple levels.…”
mentioning
confidence: 82%
“…Klisic et al (1) in this issue of JASN have added an interesting and important new finding to the complexity of our understanding of the nephrotic syndrome. They demonstrate that apical albumin directly stimulates NHE3 (sodium hydrogen exchanger 3), the major apical transporter responsible for proximal tubule sodium reabsorption.…”
mentioning
confidence: 99%
“…In the search for potential sites of sodium retention along the renal tubule, the proximal tubule has been a focus (1,4,24,34,51). Protein overload may impair its structure, causing cytoskeletal changes, lipids may become accumulated, and inflammatory factors can be induced.…”
mentioning
confidence: 99%
“…As a result, trafficking of transporters and channels may be impaired (22,32,40). Na ϩ /H ϩ exchanger 3 (NHE3)-dependent sodium reabsorption and lysosomal acidification may be affected (7,32,34), and coexpressed transport proteins such as aquaporin-1 (AQP1) and the Na ϩ -P i cotransporter IIa (NaPi-IIa) may be involved (22). Distally, regulation of the Na ϩ -K ϩ -2Cl Ϫ -cotransporter 2 (NKCC2) of thick ascending limbs (TAL) of Henle's loop may be affected as well (32), but the major distal site of retention has formerly been assigned to the collecting ducts (6,29), and recent work has been concentrated on the activation of the epithelial Na ϩ channel (ENaC) in a RAAS-independent way (3,33,38).…”
mentioning
confidence: 99%
“…Data in model systems of proximal tubule epithelia suggest possible mediation of albumin endocytosis and degradation by endosomal NHE3. [13][14][15] Intracellular [Na + ] in renal epithelia is less than 20 mmol/L, whereas basolateral [Na + ] ranges from 140 mmol/L in the cortex to as high as 300 mmol/L in the deep medulla. Basolateral NHEs undoubtedly will eject H + from the cell to the interstitium and hence are unlikely to contribute to luminal acidification.…”
Section: Na + /H + Exchangers In Mammalian Kidneymentioning
confidence: 99%